Les origines rhétoriques de la théorie des textes argumentatifs - Lipińska, Magdalena (Studia Romanica Posnaniensia, 2001)
The present paper has been written for students whose intention is to leam the basic skills of composing argumentative texts such as essays, B.A. papers and M.A. theses. As it is widely known, the structure of all persuasive forms of writing adheres to specific norms and rules, which were clearly prescribed back in antiquity and which are mostly followed in contemporary textbooks on argumentative texts. In my paper, the current French theory of the latter has been explained through description of its classical roots. The analysis focuses in particular on the stages of argumentative composition, its inherent components and the typology of argumentative texts proposed by ancient Greeks and Romans.